The effects of short term (3 weeks) testosterone treatment on serum inflammatory markers in men undergoing coronary artery stenting - (:unkn) unknown (ELSEVIER IRELAND LTD, 2006)
Objective: Inflammation markers can predict restenosis after successful intracoronary stenting. There is evidence that testosterone suppresses the expression of the inflammatory cytokines. We hypothesized that testosterone therapy after coronary stenting can reduce the inflammation markers. Methods: We selected 41 men with coronary artery disease who underwent successful stent implantation for a > 70% diameter stenosis of a major coronary artery. Patients, who had stable angina and positive exercise test results, were recruited after diagnostic coronary angiography. Twenty-five men were treated with 3 doses of i.m. testosterone administration once a week for 3 weeks following diagnostic angiography. Sixteen patients were recruited as a control group and they received standard therapy. First venous blood samples were obtained after angiography. Stents were implanted 3 weeks after diagnostic angiography. Second venous blood samples were taken 24 h after the coronary stenting. Results: Baseline biochemical or hematological parameters were similar between the control and treatment groups. After coronary stenting, free testosterone, total testosterone, and sex hormone binding globulin were significantly elevated in the testosterone group (P < 0.0001, P < 0.0001 and P=0.02; respectively). After coronary stent implantation, there was a significant increase in IL-6 and CRP levels in the control group only (P=0.02 and P=0.038), while TNF-alpha levels were increased significantly in both groups (P=0.016 and P=0.014; respectively). Statistical analysis revealed that testosterone treatment prior to stent implantation attenuated IL-6 and hs-CRP levels significantly (P=0.042 and P=0.043; respectively). Conclusions: The present study shows that 3 weeks testosterone treatment prior to intracoronary stenting results in a significant suppression in hs-CPP and IL-6 levels after the stent implantation. (c) 2005 Elsevier Ireland Ltd. All rights reserved.
Keywords: coronary stenting; testosterone; inflammatory markers; C-REACTIVE PROTEIN; CAROTID ATHEROSCLEROSIS; PLAQUE DEVELOPMENT; HYPOGONADAL MEN; STABLE ANGINA; ANDROGENS; DISEASE; THERAPY; ASSOCIATION; RESTENOSIS